Research on the application of Chinese papercutting craft in modern fashion design / Zhu Ziwei, Asliza Aris and Hasma Ahmad - Ziwei, Zhu; Aris, Asliza; Ahmad, Hasma (Universiti Teknologi MARA, Perak, 2024)
Chinese papercutting is a folk art, which is made on paper by cutting or carving, and has a history of development of thousands of years. In ancient times, its use can be roughly divided into four categories: posting, i.e., pasted on doors, windows, walls, and some furniture as decoration; embellishment, used to embellish gifts, sacrificial offerings, etc.; embroidery sampler, used for clothing, shoes, hats, and bedding embroidery patterns; printing and dyeing, as a printing plate. Since its development, the paper-cutting technique has been widely used in several artistic disciplines, by the diversity of its compositional methods and the flexibility of its expressive forms. In the field of fashion design, designers have extended the paper-cutting technique to a variety of fabrics, such as cotton, linen, and leather. By using paper-cutting techniques on different fabrics, designers can create different textures and visual effects. This study explores the aesthetic expression of paper-cutting craft in clothing by analysing its innovation and application in modern fashion design. This study uses literature review and case study methods to summarize and analyse the different ways in which the art of papercutting can be used in fashion design. Using the method of practical research, the paper-cutting technique was applied to three different fabrics, to compare the different styling effects they present. This study aims to argue the application value and development potential of the art of paper-cutting in the fashion industry through the combination of theoretical analysis and practical research.